2021
DOI: 10.3892/ijmm.2021.5014
|View full text |Cite
|
Sign up to set email alerts
|

MEIS1 and its potential as a cancer therapeutic target (Review)

Abstract: Meis homeobox 1 (Meis1) was initially discovered in 1995 as a factor involved in leukemia in an animal model. Subsequently, 2 years later, MEIS1, the human homolog, was cloned in the liver and cerebellum, and was found to be highly expressed in myeloid leukemia cells. The MEIS1 gene, located on chromosome 2p14, encodes a 390-amino acid protein with six domains. The expression of homeobox protein MEIS1 is affected by cell type, age and environmental conditions, as well as the pathological state. Certain types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Notably, most of these drugs downregulate the levels of MEIS1. More recently, Yao and colleagues [120] reported the current status on the development of MEIS1 inhibitors as therapeutic agents. 9.1.1.…”
Section: Drugs Indirectly Targeting Meis1 Though Epigenetic Control Of Its Expressionmentioning
confidence: 99%
“…Notably, most of these drugs downregulate the levels of MEIS1. More recently, Yao and colleagues [120] reported the current status on the development of MEIS1 inhibitors as therapeutic agents. 9.1.1.…”
Section: Drugs Indirectly Targeting Meis1 Though Epigenetic Control Of Its Expressionmentioning
confidence: 99%
“…24 MEIS1 is similar to HEY1 in that it binds directly to DNA to influence transcription, although unlike HEY1, it partners with homeobox proteins. 25 In addition, MEIS1::NCOA2 cases have more primitive histology with compact cells and without the degree of stromal differentiation seen in this case. This case study is the first reported primary renal spindle cell neoplasm with a HEY1::NCOA2 fusion that is distinct from mesenchymal chondrosarcoma and does not fit criteria for any other known diagnosis.…”
Section: Methodsmentioning
confidence: 71%
“…Rare NCOA2 fusions have been reported in primary renal spindle cell sarcomas, specifically MEIS1::NCOA2 fusion primitive spindle cell sarcoma involving the genitourinary and gynecological tracts 24 . MEIS1 is similar to HEY1 in that it binds directly to DNA to influence transcription, although unlike HEY1 , it partners with homeobox proteins 25 . In addition, MEIS1::NCOA2 cases have more primitive histology with compact cells and without the degree of stromal differentiation seen in this case.…”
Section: Discussionmentioning
confidence: 87%
“…As a transcription factor, MEIS1 drives cell growth [ 19 ], dysregulated MEIS1 expression contributes to tumorigenesis in multiple tumor types [ 12 , 20 , 21 , 22 , 23 ]. Due to its role in cancer cell proliferation, MEIS1 can become a molecular biomarker for cancer diagnosis and even a target for cancer therapy [ 24 ]. However, the expression levels of MEIS1 in various tumors are different [ 10 , 24 ].…”
Section: Introductionmentioning
confidence: 99%